2019
DOI: 10.1155/2019/6289831
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fat Content and Liver Enzymes Are Associated with Circulating Free and Protein-Bound Advanced Glycation End Products, Which Are Associated with Low-Grade Inflammation: The CODAM Study

Abstract: Advanced glycation end products (AGEs) accumulate in fatty livers and may contribute to low-grade inflammation (LGI), potentially via their receptor, RAGE. It is unknown if the AGE accumulation in fatty livers results in elevated circulating AGEs. In a cohort study, we investigated the association of liver fat and hepatocellular damage with circulating AGEs and soluble RAGE (sRAGE) and subsequently the association of circulating AGEs and sRAGE with LGI. Cross-sectional associations of liver fat percentage (eLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…N‐epsilon‐(carboxymethyl) lysine is a major component of advanced glycation end products (AGEs), which is a heterogeneous group of molecules formed by the nonenzymatic reaction of reducing sugars with the amino group of proteins, lipids, and nucleic acids . Soluble receptor for AGE (sRAGE) binds with AGEs as a competing factor for RAGE, and sRAGE consists of both cleaved RAGE (cRAGE) and endogenous secretory RAGE (esRAGE) which circulate in the blood .…”
Section: Discussionmentioning
confidence: 99%
“…N‐epsilon‐(carboxymethyl) lysine is a major component of advanced glycation end products (AGEs), which is a heterogeneous group of molecules formed by the nonenzymatic reaction of reducing sugars with the amino group of proteins, lipids, and nucleic acids . Soluble receptor for AGE (sRAGE) binds with AGEs as a competing factor for RAGE, and sRAGE consists of both cleaved RAGE (cRAGE) and endogenous secretory RAGE (esRAGE) which circulate in the blood .…”
Section: Discussionmentioning
confidence: 99%
“…The increased formation of amadori product and advanced glycation end product leads to direct inflammation in liver by various types of signaling pathways( (Hyogo & Yamagishi, 2008) (Bijnen et al, 2019)). HMF is also responsible for the mutation of important gene in liver .…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in the systematic review reported data on 1844 participants (909 with NAFLD, 169 with ALD and 766 healthy controls). Three studies focused on ALD [37][38][39] and eight studies on NAFLD [29][30][31][32][33][34][35][36]. In studies on ALD, the diagnosis was confirmed with a biopsy.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The number of studies obtained for each comparison was too small to assess publication bias using statistical methods such as Egger's test. [30,32,34,36].…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation